Античные мифы в литературе рубежа XX–XXI вв.: функции и варианты использования - Колесник, Диана Максимовна (SlavVaria, 2026)
Ancient myths in literature at the turn of the XX–XXI centuries: functions and ways of usage. Literature of the XX–XXI cc. is highly characterized by the turn to mythology. Neomythology of the XXth c. is followed by the post-mythology of the turn of the centuries, which is marked by demythologization and remythologization: antic plots serve as a prism for the analysis of modern problems and are used to create fantastic worlds. This tendency are demonstrated on the basis of novels by Russian and American writers (K. Bulychev, V. Protalin; R. Riordan, S. Collins, M. Miller).